Analisis Buku Ajar “Kalamuna” Pengajaran Bahasa Arab di Pusat Studi Bahasa Asing - Ulfah, Yeniati (Universitas KH. Mukhtar Syafaat, 2024)
Analyzing textbooks is very important in order to improve the quality of textbooks. The purpose of the analysis is to determine the needs of users, namely lecturers and students, for the textbook. This research is qualitative, this type of research is classified as library research. The data that researchers obtained was qualitative in the form of texts or readings contained in the